Evaluating the Effects of Feature set and Hyperparameter Optimization on sEMG-Based Gesture Recognition - Lima, Gabriel Molina de; Rossi, André L. D.; Mendes Junior, José Jair Alves; Campos, Daniel Prado; Mantovani, Rafael Gomes (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2025.11792, 2025)
Gesture recognition using myoelectric signals (sEMG) is a powerful tool for Human-Machine Interfaces (HMIs). This study investigates the classification of sEMG signals with varying sets of gestures and predictive features using Bayesian Optimization for hyperparameter tuning of Machine Learning (ML) algorithms employed for this task. Experiments were conducted on the Ninapro DB2 and DB3 datasets, covering data from both intact and amputated individuals and exploring different ML algorithms. Even though Support Vector Machines (SVMs) showed the most notable improvement through hyperparameter tuning, the best experimental results were achieved by the Random Forest (RF) classifier on both datasets, with an average F-Score of 0.853 in DB2 and 0.720 in DB3, using only five gestures and nine features. Overall, a larger feature set enhanced signal representation, particularly in reduced gesture sets, while data from amputated individuals posed greater classification challenges.